The Evolution of Potential VAT Revenues and C-Efficiency in Advanced Economies - Ueda, Junji (IMF Working Papers; Working Paper ;, 2017)
To understand the cyclical movements of value-added tax (VAT) revenues in advanced economies, this paper analyzes changes in the C-efficiency ratio by decomposing it into changes in the compliance and policy gaps between 2000 and 2014. The results from a panel of EU member countries and Japan suggest that the cyclicality of C-efficiency is explained by the correlation of both gaps with the output gap. The cyclicality of the compliance gap appears to be short lived, and larger in countries with high compliance gaps. The cyclicality of the policy gaps largely reflects not changes in policy parameters, but rather, behavior-induced changes, notably in government consumption and, to a lesser degree, in the composition of household consumption.